Controlled Release of Highly Hydrophilic Drugs from Novel Poly(Magnesium Acrylate) Matrix Tablets - Rebeca Simancas-Herbada; Ana Fernández-Carballido; Juan Aparicio-Blanco; Karla Slowing; Jorge Rubio-Retama; Enrique López-Cabarcos; Ana-Isabel (MDPI AG, 2020)
The potential of a new poly(magnesium acrylate) hydrogel (PAMgA) as a pharmaceutical excipient for the elaboration of matrix tablets for the extended release of highly hydrophilic drugs was evaluated. The polymer was synthetized with two different crosslinking degrees that were characterized by FTIR and DSC. Their acute oral toxicity was determined in a mouse model, showing no toxicity at doses up to 10 g/kg. Matrix tablets were prepared using metformin hydrochloride as a model drug and the mechanisms involved in drug release (swelling and/or erosion) were investigated using biorrelevant media. This new hydrogel effectively controlled the release of small and highly hydrophilic molecules as metformin, when formulated in matrix tablets for oral administration. The rate of metformin release from PAMgA matrices was mainly controlled by its diffusion through the gel layer (Fickian diffusion). The swelling capacity and the erosion of the matrix tablets influenced the metformin release rate, that was slower at pH 6.8, where polymer swelling is more intensive, than in gastric medium, where matrix erosion is slightly more rapid. The crosslinking degree of the polymer significantly influenced its swelling capacity in acid pH, where swelling is moderate, but not in intestinal fluid, where swelling is more intense.